Feasibility of an Intervention to Support Hearing and Vision in Dementia: The SENSE‐Cog Field Trial. Issue 7 (29th April 2019) - Hooper, Emma; Simkin, Zoe; Abrams, Harvey; Camacho, Elizabeth; Charalambous, Anna Pavlina; Collin, Fideline; Constantinidou, Fofi; Dawes, Piers; Elliott, Rachel; Falkingham, Sue; Frison, Eric; Hann, Mark; et al.
Abstract : Objectives: People with dementia (PwD) frequently experience hearing and vision impairment that is underrecognized and undertreated, resulting in reduced quality of life. Managing these impairments may be an important strategy to improve outcomes in PwD. Our objective was to field‐trial a multifaceted sensory intervention (SI) to enhance hearing and vision in PwD. Design: An international single‐arm open‐label feasibility, acceptability, and tolerability study. Setting: Home‐based setting in the United Kingdom, France, and Cyprus. Participants: Adults aged 60 years and older with mild‐to‐moderate dementia and uncorrected or suboptimally corrected hearing and/or vision impairment, and their study partners (n = 19 dyads). Intervention: A sensory intervention (SI), comprising assessment of hearing and vision, fitting of corrective devices (glasses, hearing aids), and home‐based support from a sensory support therapist for device adherence and maintenance, communication training, referral to support services, environmental sensory modification, and optimization of social inclusion. Measurements: Ratings of study procedure feasibility, and intervention acceptability/tolerability, ascertained through questionnaires, participant diaries, therapist logbooks, and semistructured interviews. Results: We successfully delivered all intervention components, and these were received and enacted as intended in all those who completed the intervention. No serious adverse events were reported. Acceptability (ie, understanding, motivation, sense of achievement) and tolerability (ie, effort, fatigue) ratings of the intervention were within a priori target ranges. We met recruitment and retention (93.8%) targets in two of the three sites. Participants completed more than 95% of diary entries, representing minimal missing data. Delays in the logistics circuit for the assessment and delivery of hearing aids and glasses were identified, requiring modification. The need for minor modifications to some outcome measures and the inclusion criteria were identified. Conclusion: This is the first study combining home‐based hearing and vision remediation in PwD. The positive feasibility, acceptability, and tolerability findings suggest that a full‐scale efficacy trial, with certain modifications, is achievable.